The state of biomechanics of posture and features of somatometric indicators in women of the second period of mature age - Demokhin , D.; Asauliuk , I. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. The sublimation of advanced ideas of science in the field of physical culture and sports rehabilitation into a strategy for the recreation of mature women involves the creation and implementation of effective innovative technologies. For the most part, scientific research in the field of correction of postural biomechanics disorders is focused on the study of the effectiveness of health technologies with women in the first period of adult-hood. The scientific and methodological dimension of the relevance of the work is determined by the inconsistency between the need to substantiate a differentiated approach in the process of physical culture and sports rehabilitation with women aged 36-40 with different types of postural biomechanics disorders and the inadequate methodological development of this issue. The purpose of the study is to determine the peculiarities of women’s posture and indicators of their biogeometric profile. Research methods: theoretical analysis of special scientific and methodological literature, pedagogical ex-periment, screening of the state of biogeometric profile of women’s posture using the “APECS AI” programme, statistical. The results. Objectively assessing the realities of today, we have to state that the prevalence of health disorders is gradually increasing from “younger” to “older” age groups of women. Behavioural factors that have a negative impact on women’s health include a decrease in their physical activity with age and a weak commitment to diet. Modern biomechanical research focuses on the development of correctional and preventive programmes for people with postural disorders. The data of the pedagogical experiment allowed us to identify specific features of the bio-mechanics of posture of women aged 36-40. Conclusions. It has been empirically determined that among women aged 36 – 37, 23,08% of people demonstrate normal posture, 38,46% of people – scoliotic posture and 38,46% of people – round back; among women aged 38 – 40, 16,67% of people demonstrate normal posture, 38,88% of people– scoliotic posture, and 44,44% of people– round back. Based on the results of comparing the indicators of the biogeometric profile of posture (head angle in the sagittal plane, symmetry of the shoulder girdle in the sagittal and frontal planes, torso angles in the sagittal and frontal planes), women with normal posture, with a round back and with scoliotic posture, we can state that there is no statistically significant difference between these indicators of women aged 36 – 37 and 38 – 40 (p>0,05). The results of non-parametric analysis of variance according to the Craskell-Wallis criterion showed that posture is a factor for all indicators of the biogeometric posture profile of women aged 36 – 37 (p<0,05), except for the indicator «Trunk angle», the value of which does not depend on the type of posture (p>0,05). At the same time, according to the results of non-parametric analysis of variance.